MUC22, HLA-A, and HLA-DOB variants and COVID-19 in resilient super-agers from Brazil - Castelli, Erick C.; de Castro, Mateus V.; Naslavsky, Michel S.; Scliar, Marilia O.; Silva, Nayane S. B.; Pereira, Raphaela N.; Ciriaco, Viviane A. O.; Castro, Camila F. B.; Mendes-Junior, Celso T.; Silveira, Etiele de S.; de Oliveira, Iuri M.; Antonio, Eduardo C.; et al. (Frontiers in Immunology, 2022)
Background: Although aging correlates with a worse prognosis for Covid-19, super elderly still unvaccinated individuals presenting mild or no symptoms have been reported worldwide. Most of the reported genetic variants responsible for increased disease susceptibility are associated with immune response, involving type I IFN immunity and modulation; HLA cluster genes; inflammasome activation; genes of interleukins; and chemokines receptors. On the other hand, little is known about the resistance mechanisms against SARS-CoV-2 infection. Here, we addressed polymorphisms in the MHC region associated with Covid-19 outcome in super elderly resilient patients as compared to younger patients with a severe outcome. Methods: SARS-CoV-2 infection was confirmed by RT-PCR test. Aiming to identify candidate genes associated with host resistance, we investigated 87 individuals older than 90 years who recovered from Covid-19 with mild symptoms or who remained asymptomatic following positive test for SARS-CoV-2 as compared to 55 individuals younger than 60 years who had a severe disease or died due to Covid-19, as well as to the general elderly population from the same city. Whole-exome sequencing and an in-depth analysis of the MHC region was performed. All samples were collected in early 2020 and before the local vaccination programs started. Results: We found that the resilient super elderly group displayed a higher frequency of some missense variants in the MUC22 gene (a member of the mucins’ family) as one of the strongest signals in the MHC region as compared to the severe Covid-19 group and the general elderly control population. For example, the missense variant rs62399430 at MUC22 is two times more frequent among the resilient super elderly (p = 0.00002, OR = 2.24). Conclusion: Since the pro-inflammatory basal state in the elderly may enhance the susceptibility to severe Covid-19, we hypothesized that MUC22 might play an important protective role against severe Covid-19, by reducing overactive immune responses in the senior population.